EXPLORATORY DATA ANALYSIS ON HOUSEHOLD EXPENDITURE SURVEY 1998 AND 2014 - Najdi, Nur Farah Najeeha; Khairul Adlee, Nurul Faziera; Adnan, Afnan Aizzat; Mustafa Khalid, Nur Izyan; Ismail, Suzilah (Journal of Human Capital Development (JHCD), 2019)
Household Expenditure Survey (HES) was utilized to accumulate information on the level and patterns of consumption expenditure of private households. It was additionally used to update the weighting patterns and to decide the items in the basket of goods and services for the compilation of the Consumer Price Index for Malaysia. The primary goals of HES are to assemble information on the level and pattern of consumption expenditure by household on a comprehensive range of goods and services. It additionally to decide the goods and services to be included into the basket of the Consumer Price Index (CPI) and to update the CPI weights which is a proportion of expansion rate in the country. Hence, this study is conducted based on HES information gathered on 1998 and 2014. The objectives of this study are to implement Exploratory Data Analysis (EDA) approach on HES data for the year 1998 and 2014 and to define who is the good spender and the bad spender is based on their income and expenditure. Keywords: Household Expenditure Survey (HES), Exploratory Data Analysis (EDA), expenditure, income